Solution processed high band-gap CuInGaS2 thin film for solar cell applications - Park, Se Jin; Cho, Jin Woo; Lee, Joong Kee; Shin, Keeshik; Kim, Ji-Hyun; Min, Byoung Koun (WILEY, 2014)
A high band-gap (similar to 1.55eV) chalcopyrite compound film (CuInGaS2) was synthesized by a precursor solution-based coating method with an oxidation and a sulfurization heat treatment process. The film revealed two distinct morphologies: a densely packed bulk layer and a rough surface layer. We found that the rough surface is attributed to the formation of Ga deficient CuInGaS2 crystallites. Because of the high band-gap optical property of the CuInGaS2 absorber film, a solar cell device with this film showed a relatively high open circuit voltage (similar to 787mV) with a power conversion efficiency of 8.28% under standard irradiation conditions. Copyright (c) 2013 John Wiley & Sons, Ltd.
Keywords: LOW-COST